The Crime of Disseminating Terrorism-Related Propaganda in Turkey: An 'Exceptional' Case for the Concrete Endangerment Approach? - Sevdiren, Oznur (Springer, 2025)
Since its inception in 1991, Article 7/2 of Turkey's Anti-Terrorism Law criminalising propaganda in support of terrorist organisations has undergone several changes and has been subject to differing interpretations. In 2013, the Turkish legislature significantly limited its scope in line with European Court of Human Rights (ECHR) jurisprudence. Under the current provision, only propaganda that praises, encourages, or justifies the methods used by the terrorist organisation, which 'comprise violence, force, or threat', would be penalised. This change in the law and the driving governmental policy was subsequently echoed in the case law of the Court of Cassation in Turkey. In numerous decisions, drawing from the ECHR case law, the court demanded an examination of whether the act in question had caused a 'clear and imminent danger' to public order and security. This shift and subsequently its partial abandonment, has raised significant questions on the nature of glorification, justification and apologie crimes. Notably, in a series of landmark decisions, the Turkish Constitutional Court also authoritatively affirmed that the propaganda crime must be treated as a concrete endangerment crime. By critically examining different models of endangerment crimes and their implications in law and practice in Turkey, this study argues that such a concrete endangerment approach aligns more closely with freedom of expression and the fundamental principles of criminal law. Furthermore, this study seeks to demonstrate that, despite Turkey's exceptional characteristics, the main issues and the impact of ECHR jurisprudence and case law are relevant to comparative criminal law systems, and that some tentative conclusions can be drawn for other countries.
Keywords: [Keyword Not Available]